In Situ Rates of Carbon and Nitrogen Uptake by Phytoplankton and the Contribution of Picophytoplankton in Kongsfjorden, Svalbard - Bo Kyung Kim; Hyoung Min Joo; Jinyoung Jung; Boyeon Lee; Sun-Yong Ha (Water, 2020)
Rapid climate warming and the associated melting of glaciers in high-latitude open fjord systems can have a significant impact on biogeochemical cycles. In this study, the uptake rates of carbon and nitrogen (nitrate and ammonium) of total phytoplankton and picophytoplankton (<2 μm) were measured in Kongsfjorden in early May 2017 using the dual stable isotope technique. The daily uptake rates of total carbon and nitrogen ranged from 0.3 to 1.1 g C m−2 day−1, with a mean of 0.7 ± 0.3 g C m−2 day−1, and 0.13 to 0.17 g N m−2 day−1, with a mean of 0.16 ± 0.02 g N m−2 day−1. Microphytoplankton (20–200 μm) accounted for 68.1% of the total chlorophyll a (chl-a) concentration, while picophytoplankton (<2 μm) accounted for 19.6% of the total chl-a, with a high contribution to the carbon uptake rate (42.9%) due to its higher particulate organic carbon-to-chl-a ratio. The contributions of picophytoplankton to the total nitrogen uptake rates were 47.1 ± 10.6% for nitrate and 74.0 ± 16.7% for ammonium. Our results indicated that picophytoplankton preferred regenerated nitrogen, such as ammonium, for growth and pointed to the importance of the role played by picophytoplankton in the local carbon uptake rate during the early springtime in 2017. Although the phytoplankton community, in terms of biovolume, in all samples was dominated by diatoms and Phaeocystis sp., a higher proportion of nano- and picophytoplankton chl-a (mean ± SD = 71.3 ± 16.4%) was observed in the relatively cold and turbid surface water in the inner fjord. Phytoplankton production (carbon uptake) decreased towards the inner fjord, while nitrogen uptake increased. The contrast in carbon and nitrogen uptake is likely caused by the gradient in glacial meltwater which affects both the light regime and nutrient availability. Therefore, global warming-enhanced glacier melting might support lower primary production (carbon fixation) with higher degrees of regeneration processes in fjord systems.